KEPASTIAN HUKUM PENGATURAN PENDIRIAN PERUSAHAAN PERORANGAN TERHADAP KONSUMEN BERDASARKAN UNDANG UNDANG NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA - Rizky, M. Rizky Arianto; Diki, Diki Zukriadi (SCIENTIA JOURNAL, 2024)
Based on Article 1 point 1 of Law Number 40 of 2007 concerning limited liability companies, which was later amended by Law Number 11 of 2020 concerning job creation, it provides a different interpretation of limited liability companies. In the process, this law begins the procedure for establishing and changing a limited liability company for micro-small businesses without the parties having any form of agreement or agreement to form a business and without requiring authentic legality in the form of a notarial deed, as regulated in Government Regulation Number 8 of 2021 regarding the Company's Authorized Capital. This of course gives rise to legal consequences and consequences that are different from ordinary limited liability companies in general which are founded by more than one person. Regarding this problem, the author conducted research using a normative research type with a statutory and regulatory approach and a contextual approach. The legal materials used in this research are primary, secondary and tertiary legal materials. The results of the research show that the arrangement of individual companies is simpler than the arrangement of ordinary limited companies with different capital between each type of company. However, it can be seen that there is a lack of legal certainty due to the fact that individual companies can be used for the benefit of the company owner